How polarised is the 2019 general election? - Duffy, Bobby; Hewlett, Kirstie; Murkin, George (King's College London, 2019)
This analysis by the Policy Institute at King’s College London reveals the extent of divisions in Britain during the 2019 general election campaign.

Using data from a survey of over 2,000 adults conducted between 27 and 29 November, the analysis finds that people’s Brexit identities have grown stronger, that opposing groups have very negative views of each other and the two main parties’ leaders, and that there are widespread misperceptions about how the “other side” feels about important political issues such as the NHS and climate change.